What Anonymous can tell us about the relationship between virtual community structure and participatory form. (4th March 2017) - Halupka, Max
ABSTRACT: As a decentralised virtual community, Anonymous has been characterised by its oppositional tendencies. Helped by a collective persona and horizontal management structure, Anonymous has facilitated a myriad of differentiated agenda. However, we can observe a distinct change in its participatory form over time. So, while Anonymous, more broadly, functions as a virtual community, its means of engagement has shifted from a social movement to a decentralised cell network. This article explores the relationship between these changes, and its evolution as a virtual community. Drawing upon Iriberri and Leroy's [(2009 ) "A Life-Cycle Perspective on Online Community Success." ACM Computing Surveys (CSUR) 41 (2): 1–29] life cycle framework, the article maps Anonymous' development and identifies the structural changes that have led to this transformation in its modes of participation.